Improved oxygenation with prostaglandin F2alpha with and without inhaled nitric oxide in dogs - Marshall, B E; Chen, L; Frasch, H F; Hanson, C W; Marshall, C (Journal of applied physiology (1985), 1998)
Dogs of mixed breed (n = 7) were anesthetized, right lung atelectasis was established, and the cyclooxygenase pathway was blocked with ibuprofen. Measurements of pulmonary gas exchange were performed (fractional concentration of inspired O2 = 0.95) after infusions of prostaglandin F2alpha (PGF2alpha; 2 microg . kg-1 . min-1), ventilation with nitric oxide (NO; 40 ppm), or both (PGF2alpha + NO) in random order. The arterial PO2 (PaO2) under control conditions was 117 +/- 16 Torr (shunt = 33 +/- 2.5%), was unchanged with NO alone (PaO2 = 114 +/- 17 Torr; shunt = 35.7 +/- 3. 1%), but was significantly improved with PGF2alpha alone (PaO2 = 180 +/- 28 Torr; shunt = 23.2 +/- 2.8%) and with the combination of PGF2alpha + NO (PaO2 = 202 +/- 30 Torr; shunt = 20.9 +/- 2.5%). The addition of NO did not significantly enhance the effectiveness of the PGF2alpha on PaO2. Simulation of these data in a computer model, combining pulmonary gas exchange and pulmonary blood flow, reproduced the results on the basis that vasoconstriction with PGF2alpha was maximal under hypoxia in the atelectatic lung and reduced by hyperoxia in the ventilated lung, consistent with the hypothesis of O2 dependence of PGF2alpha vasoconstriction.